A Conceptual Framework of Case-Based Moral Inquiry Learning for Prosocial Character Development in Speech-Language Pathology Students - Robby, Silmi Kapatan Inda; Rozaq, Muhammad Farhan (Communication In Research And Publications, 2025)
This study proposes a conceptual framework for integrating case-based moral inquiry learning into the speech language pathology education curriculum, with the primary aim of fostering prosocial character in students. Prosocial character, encompassing empathy, altruism, and social responsibility, is crucial for aspiring speech-language pathology professionals in delivering holistic and client-centered services. Although important, the development of this character is often not systematically structured in higher education. This framework is grounded in Kohlberg's theory of moral development and the case-based learning approach, which encourages students to analyze real ethical dilemmas, engage in discussions, and reflect on moral values within the context of speech-language pathology practice. Case-based moral inquiry learning is designed to facilitate moral reasoning, ethical decision-making, and the internalization of prosocial values through active and collaborative learning experiences. The proposed framework includes stages of case identification, moral dilemma analysis, group discussion, decision-making, and personal reflection, all tailored to the specific context of speech-language pathology. The implication of this framework is to provide guidance for speech-language pathology educational institutions to design effective pedagogical interventions in cultivating prosocial character, which will ultimately enhance the quality of services and professionalism of graduates.